2019
DOI: 10.1051/0004-6361/201834266
|View full text |Cite
|
Sign up to set email alerts
|

Probing the weak wind phenomenon in Galactic O-type giants

Abstract: Aims. Analyses of Galactic late O dwarfs (O8-O9.5V stars) raised the "weak wind problem": spectroscopic mass-loss rates (Ṁ) are up to two orders of magnitude lower than the theoretical values. We investigated the stellar and wind properties of Galactic late O giants (O8-O9.5III stars). These stars have luminosities log(L /L ) ∼ 5.2, which is the critical value (onset of weak winds) proposed in the literature. Methods. We performed a spectroscopic analysis of nine O8-O9.5III stars in the ultraviolet (UV) and op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 339 publications
(587 reference statements)
5
15
0
Order By: Relevance
“…Similar stars, with very low mass-loss rates, were found in the study of MSC-N81 by [149] who suggested that the wind-luminosity relation for dwarfs breaks down when L < 3 × 10 5 L . Similar "weak-wind" stars are found in the Galaxy [150,151] although the upper L < 2 × 10 5 limit to the phenomenon may be a little lower than in the SMC. [151] suggest that evolution may not be a crucial parameter-they found that O9-O9.5III stars also exhibited weak winds.…”
Section: Weak Windssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar stars, with very low mass-loss rates, were found in the study of MSC-N81 by [149] who suggested that the wind-luminosity relation for dwarfs breaks down when L < 3 × 10 5 L . Similar "weak-wind" stars are found in the Galaxy [150,151] although the upper L < 2 × 10 5 limit to the phenomenon may be a little lower than in the SMC. [151] suggest that evolution may not be a crucial parameter-they found that O9-O9.5III stars also exhibited weak winds.…”
Section: Weak Windssupporting
confidence: 65%
“…Similar "weak-wind" stars are found in the Galaxy [150,151] although the upper L < 2 × 10 5 limit to the phenomenon may be a little lower than in the SMC. [151] suggest that evolution may not be a crucial parameter-they found that O9-O9.5III stars also exhibited weak winds. The "weak wind" problem is also seen for non-supergiant B stars [152].…”
Section: Weak Windssupporting
confidence: 65%
“…Regarding the two excluded low-luminosity stars, these seem to indicate a weak wind effect also at Galactic metallicity. Also observational studies of Galactic dwarfs (Martins et al 2005;Marcolino et al 2009) and giants (de Almeida et al 2019) find that the onset of the weak wind problem seems to lie around log(L * /L ) ≈ 5.2, where such an onset was already indicated in the data provided by Puls et al (1996). Although our mass-loss rates in this regime are significantly lower than those of Vink 2000), they are still not as low as those derived from these observational studies.…”
Section: The Galaxymentioning
confidence: 64%
“…The Balmer lines, in particular Hα, seems to be better reproduced using a slightly higher value for the mass-loss rate (Ṁ = 4.0 × 10 −5 M yr -1 with f ∞ = 0.5). However, this difference is encompassed by the typically uncertainties onṀ found from spectroscopic analysis of massive stars in literature (see, e.g., [7]). It is beyond the scope of this paper to derive the stellar and wind parameters of P Cyg, as performed by [36] and [35].…”
Section: Comparison To Spectroscopic Datamentioning
confidence: 99%